IQTISODCHI KADRLAR TAYYORLASHDA TA’LIM XIZMATLARINING O’ZIGA XOS XUSUSIYATLARI: IQTISODCHI KADRLAR TAYYORLASHDA TA’LIM XIZMATLARINING O’ZIGA XOS XUSUSIYATLARI - Axtamov, Jamshed (FILOLOGIYA UFQLARI JURNALI, 2021)
In the article considered following main specifics of market economy as soon as : social – economical issue of market economy; analyzed tasks preparing of economical specialists; main specific steps of liberity economy.